2021
DOI: 10.1007/s11482-021-09956-0
|View full text |Cite
|
Sign up to set email alerts
|

How Trust Makes a Difference: The Impact of the First Wave of the COVID-19 Pandemic on Life Satisfaction in Germany

Abstract: The extraordinary COVID-19 pandemic is one of the most severe disruptions of human life since the end of World War II, even in rich and industrialized countries like Germany. The introduction of a rather comprehensive “lockdown” and the restriction of multiple basic civil rights have affected the population in many areas of life, like employment, economic prosperity, health and trust in public institutions. The question arises how life satisfaction is influenced by these measures in detail and whether there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
2
29
1
Order By: Relevance
“…Generally, this finding in line with our assumption that the susceptibility of well-being to "COVID-19 effects" might be domain-specific. Decline in life satisfaction due to the pandemic, which we found for some, though not all individuals, has also been reported by other studies (Bittmann, 2021;Schlomann et al, under review;Schwinger et al, 2020;Zacher & Rudolph, 2020), although there are also studies reporting stability, or even slight increase, in life satisfaction despite COVID-19 (e.g., Entringer et al, 2020;Wettstein et al, 2021).…”
Section: Covid-19-related Change In Hedonic and Eudaimonic Well-beingsupporting
confidence: 89%
See 1 more Smart Citation
“…Generally, this finding in line with our assumption that the susceptibility of well-being to "COVID-19 effects" might be domain-specific. Decline in life satisfaction due to the pandemic, which we found for some, though not all individuals, has also been reported by other studies (Bittmann, 2021;Schlomann et al, under review;Schwinger et al, 2020;Zacher & Rudolph, 2020), although there are also studies reporting stability, or even slight increase, in life satisfaction despite COVID-19 (e.g., Entringer et al, 2020;Wettstein et al, 2021).…”
Section: Covid-19-related Change In Hedonic and Eudaimonic Well-beingsupporting
confidence: 89%
“…However, according to their study, life satisfaction revealed a decline between March and May 2020. Other studies have reported lower life satisfaction in German individuals in the initial phase of the pandemic compared to pre-pandemic times such as 1-2 years prior to the pandemic onset (e.g., Bittmann 2021).…”
Section: Empirical Evidence On the Impact Of Covid-19 On Well-beingmentioning
confidence: 95%
“…Zacher and Rudolph (2020) report that among employees aged 18 and older, wellbeing declined between March and May 2020. Also, findings from the Mannheim Corona Study suggest that Germans' domain-specific satisfactions, such as the ones with work and family life, declined between September 2019 and April 2020 (Möhring et al, 2020; for similar findings, see also Bittmann, 2021;Schlomann et al, 2021). In some contrast to these findings, mean-level stability in life satisfaction between 2019 and April 2020 was observed in the Socio-Economic Panel (SOEP-CoV) study (Entringer et al, 2020).…”
Section: Covid-19: Implications For Well-beingmentioning
confidence: 89%
“…Such data are becoming increasingly available, for example, see the OECD COVID-19 Recovery Dashboard [101]. Multiple national-level observational studies report negative consequences of the pandemic on the subjective well-being and other national well-being dimensions, such as trust in government [5,23,24,88,[102][103][104]. However, these studies do not account for causal mechanisms of such effects [102].…”
Section: Discussionmentioning
confidence: 99%